Experimental and numerical study of MILD combustion in a lab-scale furnace. (August 2017) - Huang, X.; Tummers, M.J.; Roekaerts, D.J.E.M.
Abstract: Mild combustion in a lab-scale furnace has been experimentally and numerically studied. The furnace was operated with Dutch natural gas (DNG) at 10 kW and at an equivalence ratio of 0.8. OH* chemiluminescence images were taken to characterize the reaction zone. The chemiluminescence intensity is relatively low compared to conventional flames and relatively uniformly distributed in the reaction zone due to the dilution effects of recirculated burnt gases. Visible flames were not observed. To characterize the dilution effects of burnt gases on reactions, flamelets generated with diluted fuel and diluted air, instead of flamelets based on pure fuel and air, were applied in an extended Flamelet Generated Manifold (FGM) approach. Burnt gases at stoichiometric mixture fraction rather than those at global equivalence ratio were considered as diluent, which is more appropriate for furnaces operating at lean condition. The numerical simulations were performed using the open source CFD package -- OpenFOAM.